CENTRAL KALIMANTAN’S LOCAL BAMBOO MATERIALS FOR CONSTRUCTION COMPONENTS (COLUMN, RINGS, & WALL COVER) OF SIMPLE HEALTHY SUSTAINABLE HOUSE - Ave Harysakti; Indrabakti Sangalang; Fredyantoni F. Adji; Amiany; Giris Ngini (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
Slums always can be found in big cities in Indonesia, as a result of the impact of urbanization. This slum settlement is identical to the conditions of inadequate environmental infrastructure including the condition of houses that are almost uninhabitable. Physically, most of the house buildings use used materials. Materials such as wood / used beams for house frame structures, used boards mixed with used zinc and rust for walls, and used zinc (metal or plastic) and straw for roof coverings. The cumulative impact of the existence of these slums is a decrease in the visual quality of the urban built environment and a decrease in the quality of the health of the urban built environment. as a solution, it was stated that the model of the Simple Healthy Sustainable House of Local Bamboo Construction in this case bamboo that grows in Central Kalimantan.At present most of the design of cheap bamboo-based houses is using Petung Bamboo (Dendrocalamus Asper), while on the island of Kalimantan this type of bamboo has very little population. For this reason, it has been researched and modeled for sustainable healthy simple houses using local bamboo species whose populations are widely available in Central Kalimantan such as Suluk Bamboo (Gigantochloa Levis (Blanco)), Tamiang Bamboo (Schizotachyum Blumei Nees) and Yellow Bamboo (Bambusa Vulgaris Schard). The three types of bamboo are determined as a component of the Sustainable Healthy Simple Houses Construction, namely as Main Column component, Supporting Columns, Frame and Wall Coverings, and also as Ring Balk.